Chemical Composition and Biological Activities of Extracts from Pomelo Peel By-Products under Enzyme and Ultrasound-Assisted Extractions. (26th February 2020) - Van Hung, Pham; Yen Nhi, Nguyen Hai; Ting, Ling Yu; Lan Phi, Nguyen Thi
Abstract : Enzyme-assisted extraction (EAE) and ultrasound-assisted extraction (UAE) were popular methods used to extract bioactive compounds from citrus peels, by-products of fruit processing industry. In this study, the total phenolic content (TPC), total flavonoid content (TFC), naringin and hesperidin contents, and antioxidant and antimicrobial activities of the extracts from pomelo peels using the combined enzyme and ultrasound-assisted extraction (E-UAE) or ultrasound and enzyme-assisted extraction (U-EAE) technique were investigated and compared with those extracted using the EAE and UAE. The optimal EAE conditions were as follows: enzyme concentration of 2%, water-solid ratio of 40 ml/g, incubation temperature of 50°C, and extraction time of 60 min, whereas the optimal UAE conditions were ultrasonic energy of 40 kHz, water-solid ratio of 40 ml/g at room temperature, and extraction time of 60 min. The results indicate that the total phenolics, total flavonoids, naringin, and hesperidin contents of the extracts significantly increased in the following order of the extraction techniques: UAE < EAE < U-EAE < E-UAE (p < 0.05 ). The combined E-UAE technique was the most effective technique for bioactive compound extraction with the highest antioxidant and antimicrobial activities. The results also indicate that chemical composition and antioxidant and antimicrobial activities of the extracts were different depending on the pomelo species.